Update on Neuroendocrine Carcinomas of the Larynx. Issue 6 (15th August 2019) - Strosberg, Carolina; Ferlito, Alfio; Triantafyllou, Asterios; Gnepp, Douglas R; Bishop, Justin A; Hellquist, Henrik; Strojan, Primoz; Willems, Stefan M; Stenman, Göran; Rinaldo, Alessandra; Hernandez-Prera, Juan C
Abstract: Objectives: Laryngeal neuroendocrine carcinomas are heterogeneous neoplasms characterized by neuroendocrine differentiation. Their prognoses are dependent on tumor type, therefore different classifications have been developed. Moreover, other tumors have overlapping pathologic features posing a range of diagnostic possibilities. Methods: A review of the literature was performed to comprehensively understand the classification and diagnosis of these tumors. Results: We review the past and present classification systems, with emphasis to the latest 2017 World Health Organization Classification of Head and Neck Tumors. We highlight salient clinicopathologic features and discuss the presumptive etiologic role of human papilloma virus. We share a practical algorithmic approach to the diagnosis of suspected neuroendocrine neoplasms of the larynx including a novel marker for neuroendocrine differentiation, insulinoma-associated protein 1. Conclusions: Accurate diagnosis and grading of laryngeal neuroendocrine carcinomas is critical for prognostication and therapeutic decision making. The use of an algorithm is instrumental in assuring the exclusion of mimickers.